Legal Standing for Informed Consent During Referral Patient Transportation - Sumitra, Syamsul; Aryaningruh, Eunike; Jamaludin, Ahmad (PDIH Untag Semarang, 2025)
Informed consent is a fundamental legal and ethical requirement in medical practice, yet its implementation becomes challenging during the transport of referred patients, especially in emergencies when patients cannot provide direct consent. This study analyzes the legal standing and validity of informed consent in referral transport within Indonesian healthcare. Using a normative legal research method, this study examines relevant regulations such as the Health Law, Medical Practice Law, Civil Code, and the Minister of Health Regulation supported by legal doctrines and literature review. The results show that informed consent remains legally significant in-patient transport because the transfer constitutes a medical procedure with inherent risks. Ideally, consent includes explanations of the patient’s condition, referral purpose, transportation risks, and type of medical transport. However, emergency situations often require implied consent under the emergency doctrine. Challenges include limited understanding among families, time constraints, and inconsistent documentation. In conclusion, informed consent in referral transport is essential for protecting both patients and healthcare professionals. Improving SOPs, communication, and documentation systems is necessary to ensure legal compliance and patient safety.